Emerging heterologous mRNA-based booster strategies within the COVID-19 vaccine landscape. Issue 1 (31st December 2023) - Das, Rituparna; Hyer, Randall N.; Burton, Paul; Miller, Jacqueline M.; Kuter, Barbara J.
ABSTRACT: Messenger RNA (mRNA)-based vaccine platforms used for the development of mRNA-1273 and BNT162b2 have provided a robust adaptable approach to offer protection against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, as variants of concern (VoCs), such as omicron and associated sub-variants, emerge, boosting strategies must also adapt to keep pace with the changing landscape. Heterologous vaccination regimens involving the administration of booster vaccines different than the primary vaccination series offer a practical, effective, and safe approach to continue to reduce the global burden of coronavirus disease 2019 (COVID-19). To understand the immunogenicity, effectiveness, and safety of heterologous mRNA-based vaccination strategies, relevant clinical and real-world observational studies were identified and summarized. Overall, heterologous boosting strategies with mRNA-based vaccines that are currently available and those in development will play an important global role in protecting individuals from COVID-19 caused by emerging VoCs.